2018
DOI: 10.1021/acssuschemeng.8b01855
|View full text |Cite
|
Sign up to set email alerts
|

High-Pressure Microfluidization as a Green Tool for Optimizing the Mechanical Performance of All-Cellulose Composites

Abstract: We herein report the production of environmentally inspired all-cellulose composites in response to the ever-growing concern on the extensive usage of nonbiodegradable materials derived from nonrenewable resources. Hydroxypropyl methylcellulose (HPMC) was used as a film-forming matrix, while microcrystalline cellulose (MCC) was added as a reinforcement filler. Because the efficiency of fillers in transferring mechanical strength to polymer matrixes relies upon the dispersion level of the former within the latt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…While increasing the tensile strength and YM of HPMC-only films to 41 and 80%, respectively, adding 5 wt % of the BCNC through a high-energy mixing process did not affect (p > 0.05) the EB (Figure 4b), although some of the treatments did reduce film extensibility, as reported elsewhere for similar systems. 7,29 The aforementioned treatment also lessened (p < 0.05) the WVP of HPMC-only films in 22.5%, whereas none of the others affected (p > 0.05) the WVP of pristine HPMC films. Because low WVP values are typical of good barriers to moisture, one may conclude that HPMC films may represent a better barrier material when filled with the BCNC, though depending on the filler content and mixing protocol.…”
Section: ■ Results and Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…While increasing the tensile strength and YM of HPMC-only films to 41 and 80%, respectively, adding 5 wt % of the BCNC through a high-energy mixing process did not affect (p > 0.05) the EB (Figure 4b), although some of the treatments did reduce film extensibility, as reported elsewhere for similar systems. 7,29 The aforementioned treatment also lessened (p < 0.05) the WVP of HPMC-only films in 22.5%, whereas none of the others affected (p > 0.05) the WVP of pristine HPMC films. Because low WVP values are typical of good barriers to moisture, one may conclude that HPMC films may represent a better barrier material when filled with the BCNC, though depending on the filler content and mixing protocol.…”
Section: ■ Results and Discussionmentioning
confidence: 92%
“…This is a clear outcome of the filler-in-matrix state of dispersion, which must be sufficiently high to prevent particle aggregation that is known to create stress raisers as well as to decrease the specific filler/matrix interfacial area, impairing the load transfer efficiency. 7 Comparably, Salari et al 30 found CNCs to reinforce chitosan films when the particles were homogeneously dispersed within the nanocomposite, favoring filler/ matrix interactions and the effective matrix-to-filler load transfer. A similar effect was observed on the tensile strength of HPMC-only films, which became more resistant (p < 0.05) upon BCNC addition followed by a high-energy procedure, regardless of the BCNC-to-HPMC ratio.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations